Monitoring of bacteria biofilms forming process by in-situ impedimetric biosensor chip - Liu, Lulu; Xu, Yi; Cui, Feiyun; Xia, Ye; Chen, Li; Mou, Xiaojing; Lv, Junjiang (Biosensors & bioelectronics, 2018)
A biosensor chip integrated interdigital microelectrodes was proposed and applied to monitor the formation process of Salmonella and E. coli biofilms in this paper. The biosensor chip was composed of a glass substrate with interdigital microelectrodes and PDMS layer with micro cavities. The electrochemical impedance spectroscopy (EIS) of Salmonella and E. coli biofilms was measured by the biosensor chip using alternating voltage of 100 mv in the frequency range from 1 Hz to 100 kHz for 48 h. It was illustrated that the changes of impedance spectroscopy of biofilms occurred with culture time. Furthermore, impedance spectroscopy of biofilms was fitted by an equivalent circuit model including the biofilms capacitance (Cb) and the biofilms resistance (Rb) parameters. The results indicated that the Cb presented a tendency to decrease first and then rise with culture time, while the Rb was in the opposite direction. These changing trends were consistent with the formation process of biofilms that bacteria adhered to electrodes surface, and then formed mature biofilms, finally escaped from biofilms. In addition, it was also demonstrated that the changing trends of Cb and Rb with culture time were quite different between Salmonella and E. coli. The results obtained by impedance detection were in accordance with the results of using crystal violet staining to analyze biofilms formation process, under the same conditions for bacterial culture. The biosensor chip provided a promising platform for further study of biofilms owing to its unique advantages of real time, continuity, and non-invasion for bacteria biofilms detection and in-situ monitoring. •An impedance biosensor chip was designed to monitor biofilms forming process.•Periodic characteristics of biofilms were discriminated by changes of electrochemical parameters.•The method based on the biosensor chip had advantages of real time, continuity, and non-invasion.